Resiliensi Terhadap Ideologi Radikalisme di Pesantren Darussalam Lirboyo Kediri - Sugianto, Anto (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
The attention given by the government at the end of this decade to islamic boarding school, such as the determining of October 22 as the day of Santri, the islamic boarding school law, equality (Muaddalah) Ma'had 'Aly with one or two degrees, shows that in reality and in its field, islamic boarding school has a fairly important role. for the resilience, sustainability and integrity of the Unitary State of the Republic of Indonesia (NKRI). And base on the assumption that the islamic boarding school has never been exposed to radicalism, which makes researchers interested in focusing this research on how the model of the resilience of the Lirboyo Islamic boarding school Darussalam unit toward the ideology of radicalism and the application of this resilience to alumnus. Field research with a descriptive qualitative analysis approach, from primary and secondary sources, using observation, interviews, and documentation techniques then reducing, presenting, verifying data, and testing credibility with extended observations, triangulation, increased accuracy, negative case analysis, and our member checks also use in this study. The results of this study: (1) The Darussalam islamic boarding school resilience model is carried out by preventing contact with radical groups, delegitimizing radical ideologies, eliminating prejudice with other groups and the relationship between islamic boarding school and the government structure. (2) This resilience makes the attitude of islamic boarding school alumnus to be anti-violent, tolerant and have good relations with the government. This model and application become the islamic boarding school’s social capital with levels in the form of social bonding, social bridging and social linking